Referenzrahmen für eigenständige digitale Wissenschaftskommunikation durch Forschende - Claudia Frick; Melanie E.-H. Seltmann (Zeitschrift für digitale Geisteswissenschaften)
Science communication, as the communication in which science and society enter into an exchange with each other about scientific problems, is becoming more and more important. In contrast to scholarly communication, where science communicates within scientific communities (science-to-science), science communication uses other mechanisms, platforms and communication methods (science-to-public and public-to-science). Due to social media, the barrier for direct exchange and entry into science communication has become lower and lower for scholars. However, certain methodological, technical and social competencies are needed not only to initiate this exchange, but also to actively enter into it and accompany it. So far, these competences have rarely been part of academic training and have not been recorded and presented in a structured way. With a focus on independent digital science communication, i. e. researchers creating their own digital communication formats, a corresponding reference framework will be developed in this working paper.